In the shadow of Billy the Kid Susan McSween and the Lincoln County War - Chamberlain, Kathleen (Kathleen P.) (University of New Mexico Press, 2013)
"Chamberlain argues that the focus on Billy the Kid has discouraged broader interpretations of the Lincoln County War; she provides a woman's perspective of the historic event and places Susan McSween's life and legacy into the larger context of New Mexico history and of women's experiences in the late nineteenth and early twentieth century Southwest"--Provided by publisher.